(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Biosimilar medicines are biologic treatments that are clinically equivalent to a previously approved reference biological product in terms of quality, efficacy, safety, and immunogenicity, and have the potential to lower biologic costs. Given the growing number of oncology biosimilars, it is critical to quantify the economic impact of biosimilars in oncology, using trastuzumab and rituximab as examples, which have the highest budgetary impact in Oncology Units, respectively. Biologics are important in cancer treatment not only because of their therapeutic effects and ability to improve outcomes, but also because they are supportive care agents. These are more difficult to make and take longer to get to market. Because biologics are much more expensive than small-molecule medications, their usage has put a growing economic strain on healthcare systems around the world. Biosimilars are intended to be substantially similar to existing branded biologics, but because biologics cannot be precisely duplicated, they should not be referred to as generic, exact copies of the originator biologic. As patent protection for some of the most extensively used biologics begins to expire, biosimilars have the potential to enhance access and give lower-cost options for cancer treatment.